Bifidogenic effect and in vitro immunomodulatory roles of melibiose-derived oligosaccharides produced by the acceptor reaction of glucansucrase E81 - Ispirli, Humeyra; Kaya, Yasemin; Dertli, Enes (ELSEVIER SCI LTD, 2020)
Glucansucrases are responsible for the production of alpha-glucans using sucrose as the substrate. Glucansucrases may also produce different oligosaccharides by transferring the glucose moiety from sucrose to a variety carbohydrates acting as acceptor nucleophile. In this study, melibiose-derived oligosaccharides were produced by the glucansucrase from Lactobacillus reuteri E81 expressed without the N-terminal region (GtfA-Delta N). The reaction products were characterized by TLC, LC-MS and NMR analysis and it was found that GtfA-Delta N synthesized melibiose-derived oligosaccharides (DP3 and DP4) by adding glucose units through alpha 1- > 3 or 1- > 6 glycosidic bond. The functional characteristics of these melibiose-derived oligosaccharides were determined by testing the immune-modulatory functions in HT-29 cells and testing their growth promoting effects for important probiotic and pathogenic strains. The melibiose-derived oligosaccharides triggered the production of anti-inflammatory cytokine IL-10 and pro-inflammatory cytokine TNF-alpha depending on their concentrations. Finally, melibiose-derived oligosaccharides showed bifidogenic effect as potential prebiotics.
Keywords: Glucansucrase; Melibiose-Derived oligosaccharides; Immune-Modulation; Prebiotics; Functional roles; PREBIOTIC PROPERTIES; ALPHA; FERMENTATION; POLYSACCHARIDES; MODULATION; GLUCAN; GOS; Biochemistry & Molecular Biology; Biotechnology & Applied Microbiology; Engineering